Strategies of rendering difficult syntactic structures in English-Arabic simultaneous interpreting - Abdulameer, Muhannad Hadi Abdulameer (2022)
When conducted between linguistically different language pairs, simultaneous interpreting encapsulates difficulties when choosing the strategies to be used with certain syntactic structures. The present study is a corpus-based study which examines how simultaneous interpreters employ certain interpreting strategies rather than others when rendering noun phrases and numbers in English-Arabic simultaneous interpreting. In light of the emerging conditions posed by the corona virus pandemic hitting the world and the urgent need to carry out interpreting tasks remotely, the present study aims to identify the categories of noun phrases and numbers that cause difficulties when rendered from English into Arabic through applying Quirk et al., (1985) and the strategies employed to render them through applying Kohn and Kalina (1996). To address the issues focused on in this study, a parallel unidirectional corpus of English source speeches on briefings about the Corona virus around the world with their Arabic renditions was compiled to constitute the data of the study. The findings of the study indicate that simultaneous interpreters employed nine interpreting strategies when rendering noun phrases. The employed strategies are parallelization, omission, deviation, condensation, substitution, paraphrasing, expansion, repair, and elaboration. Whereas, numbers were interpreted employing three interpreting strategies; parallelization, deviation, and omission. The findings also show that a new interpreting strategy has emerged. The strategy was termed as deviation, in which the interpreter omits a particular syntactic structure and adds irrelevant information in order to avoid being silent. Additionally, the data analysis reveals that the strategies of parallelization, condensation, substitution, paraphrasing, expansion, repair, and elaboration are appropriate for rendering noun phrases, whereas, numbers are only appropriately rendered by employing the strategy of parallelization. These findings were validated by inter-raters proving that the identification of difficult categories as well as the strategies employed to render each of them along with the appropriate strategies of rendition are appropriately conducted. Based on the findings of the present study, the researcher proposed many recommendations and suggestions in order to help simultaneous interpreters overcome such difficulties.